The Use of Adjacency Pair Patterns in â€œAncora Meetâ€ Interview with Nadiem Anwar Makarim - Beni Saptiyanto; Dwi Rukmini; Henrikus Joko Yulianto (English Education Journal, 2022)
Conversation Analysis is an issue of Pragmatics. It is a way to analyze a conversation by its elements, such as turn-taking and adjacency pair produced by the speakers. In this present study, we conducted research in the field of conversation analysis. More specifically, we investigated the adjacency pair patterns, the meaning of the patterns, and the implicature of the patterns in the spoken interaction of the Ancora Meet discussion with Nadiem Anwar Makarim, Minister of Education and Culture of Indonesia, the Republic of Indonesia. This research investigates how adjacency pairs patterned in Ancora Meet’s interview with Nadiem Anwar Makarim, how meaning is made through the patterns, and how the implicature resulted from using the patterns. This present study used a qualitative method. We found eight patterns of adjacency pair construct in Ancora Meet, and then three maxims were realized in the discussion. This study also reveals some patterns. Individuals prefer to communicate information implicitly rather than explicitly. Particularised dialogue implicature dominance in the discussion is evidence that speakers are connected to the context to implicate utterances in their current conversation. The particularised conversation implicature’s violation of the maxim is evidence of a significant relationship between context and cooperative principles. Conversation implicatures are almost always connected to the context. Finally, we discovered 42 instances of Minister Nadiem’s implicature, demonstrating that, for the most part, conversational implicature is always connected to context. Meanwhile, in practical contribution, this research can be used as a reference in teaching English, especially speaking.